An experimental study on oxygen isotope exchange reaction between CAI melt and low-pressure water vapor under simulated Solar nebular conditions. (1st December 2021) - Yamamoto, Daiki; Kawasaki, Noriyuki; Tachibana, Shogo; Kamibayashi, Michiru; Yurimoto, Hisayoshi
Abstract: Calcium-aluminum-rich inclusions (CAIs) are known as the oldest high-temperature mineral assemblages of the Solar System. The CAIs record thermal events that occurred during the earliest epochs of the Solar System formation in the form of heterogeneous oxygen isotopic distributions between and within their constituent minerals. Here, we explored the kinetics of oxygen isotope exchange during partial melting events of CAIs by conducting oxygen isotope exchange experiments between type B CAI-like silicate melt and 18 O-enriched water vapor ( P H2O  = 5 × 10 −2 Pa) at 1420 °C. We found that the oxygen isotope exchange between CAI melt and water vapor proceeds at competing rates with surface isotope exchange and self-diffusion of oxygen in the melt under the experimental conditions. The 18 O concentration profiles were well fitted with the three-dimensional spherical diffusion model with a time-dependent surface concentration. We determined the self-diffusion coefficient of oxygen to be ∼1.62 × 10 −11 m 2 s −1, and the oxygen isotope exchange efficiency on the melt surface was found to be ∼0.28 in colliding water molecules. These kinetic parameters suggest that oxygen isotope exchange rate between cm-sized CAI melt droplets and water vapor is dominantly controlled by the supply of water molecules to the melt surface at P H2O < ∼10 −2 Pa and by self-diffusion of oxygen in the melt at P H2O > ∼1 Pa at temperatures above the melilite liquidus (1420–1540 °C). To form type B CAIs containing 16 O-poor melilite by oxygen isotope exchange between CAI melt and disk water vapor, the CAIs should have been heated for at least a few days at P H2O  > 10 −2 Pa above temperatures of the melilite liquidus in the protosolar disk. The larger timescale of oxygen isotopic equilibrium between CAI melt and H2 O compared to that between H2 O and CO in the gas phase suggests that the bulk oxygen isotopic compositions of ambient gas at ∼1400 °C in the type B CAI-forming region is preserved in the oxygen isotopic compositions of type B CAI melilite. Based on the observed oxygen isotopic composition, we suggest that a typical type B1 CAI (TS34) from Allende was cooled at a rate of ∼0.1–0.5 K h −1 during fassaite crystallization.